A kind of negative hard water corrosion inhibitor and preparation method thereof
By using negative hard water corrosion inhibitors prepared from polyepoxysuccinic acid and other raw materials, combined with the silicone film formation technology of synergists, the problems of poor slow-release effect and high pollution in the existing technology have been solved, and efficient reduction has been achieved. The effect of corrosion on metal materials.
Patent Information
- Application Number
- CN202410061408.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-01-16
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2044-01-16
AI Technical Summary
At this stage, the sustained release effect of negative hard water corrosion inhibitors is poor and have high contamination, making it difficult to effectively reduce the corrosion of metal materials.
The negative hard water corrosion inhibitor is prepared through specific mixing and reaction steps using raw materials such as polyepoxysuccinic acid, scale inhibitor and dispersant, zinc salt, organic carboxylate, azoles and synergists. The synergist is produced through the reaction of maleic anhydride, urea and other raw materials. It contains a quaternary ammonium salt structure and a hyperbranched organic silicon segment, which can form a dense organic silicon film to prevent the metal surface from directly contacting water.
It achieves the effective slow release of negative hard water corrosion inhibitor, significantly reduces the corrosion rate of metal materials, reduces pollution, and improves the use effect of the product.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of corrosion inhibitor preparation, and in particular to a negative hard water corrosion inhibitor and a preparation method thereof. Background Art
[0002] Water is the lifeblood of industry. Water is the first choice for industrial enterprises as a cooling medium. Scaling, corrosion and microorganisms are the three major factors in industrial water treatment. High alkalinity and low hardness water is a typical water quality with strong corrosiveness in the circulating water system. This type of water is used in many industrial enterprises. Ordinary water contains Ca 2+ Mg 2+ Hardness components such as iron and steel can be deposited on the metal surface to form a less dense and thin protective layer, reducing the contact between corrosive substances such as oxygen in the water and the metal, thereby reducing corrosion to the metal. The hardness of low-hardness water is very low and can no longer form a protective layer. The metal is in direct contact with water and is therefore more susceptible to corrosion. Currently, circulating water systems with high alkalinity and low hardness water are basically based on phosphorus-based water treatment agents. Due to the scale and corrosion characteristics of this type of water, the formula is mostly based on phosphorus-based agents that have both corrosion and scale inhibition effects. At the same time, in order to control the occurrence of corrosion, the amount of phosphorus added is relatively high. In view of the characteristics of high alkalinity and low hardness water, a special corrosion inhibitor is urgently needed to reduce the corrosion of metal materials. Summary of the invention
[0003] The purpose of the present invention is to provide a negative hard water corrosion inhibitor and a preparation method thereof, so as to solve the problem that the negative hard water corrosion inhibitor at present has good slow-release effect but high pollution.
[0004] The purpose of the present invention can be achieved by the following technical solutions:
[0005] A method for preparing a negative hard water corrosion inhibitor comprises the following steps:
[0006] Weigh the following raw materials in percentage: 5-15% polyepoxysuccinic acid, 5-15% scale inhibitor and dispersant, 5-10% zinc salt, 10-40% organic carboxylate, 0.1-0.5% azole and 10-15% synergist, and the balance is water, mix the raw materials evenly to prepare a negative hard water corrosion inhibitor.
[0007] The polyepoxysuccinic acid is a commercially available liquid preparation with a solid content of 40% and a degree of polymerization n ranging from an integer of 10 to 50; the scale inhibitor and dispersant is an acrylic copolymer with AMPS; the zinc salt is one of zinc chloride or zinc sulfate; the organic carboxylate is one of polyacrylic acid, benzoic acid and a sodium salt of a copolymer containing a sulfonic acid group or carboxymethyl cellulose; and the azole is one of benzotriazole and mercaptobenzoxazole.
[0008] Further, the synergist is prepared by the following steps:
[0009] Step A1: maleic anhydride, deionized water and urea are mixed, stirred for 40-50 min at a speed of 120-150 r / min and a temperature of 60-70° C., then heated to 130-140° C., a mixed acid solution is added, and the temperature is raised to 180-185° C. to react for 2-3 h to obtain polysuccinimide;
[0010] Step A2: polysuccinimide, diethylenetriamine and deionized water are uniformly mixed, stirred and sodium hydroxide solution is added at a speed of 150-200 r / min and a temperature of 60-65° C., reacted for 15-20 hours, and then the pH value is adjusted to neutral to obtain a modifier;
[0011] Step A3: Mix the hyperbranched amine, cyanuric chloride, sodium hydroxide and acetone evenly, react for 2-3 hours at a speed of 120-150 r / min and a temperature of 0-5° C., add a modifier, raise the temperature to 80-90° C., and continue to react for 2-3 hours to obtain a synergist.
[0012] Furthermore, the dosage ratio of maleic anhydride, deionized water, urea and mixed acid in step A1 is 100 mmol:10 mL:70 mmol:1 mL, and the mixed acid is phosphoric acid and sulfuric acid mixed in a volume ratio of 1:1.
[0013] Furthermore, the usage ratio of the polysuccinimide, diethylenetriamine and sodium hydroxide solution in step A2 is 2g:1.5g:5mL, and the concentration of the sodium hydroxide solution is 2.5mol / L.
[0014] Furthermore, the amount ratio of the hyperbranched amine, cyanuric chloride, sodium hydroxide and modifier described in step A3 is 2g:10mmol:30mmol:20mmol.
[0015] Further, the hyperbranched amine is prepared by the following steps:
[0016] Step B1: octamethylcyclotetrasiloxane, tetramethyltetrahydrocyclotetrasiloxane, 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane and ion exchange resin CT175 are uniformly mixed, nitrogen is introduced for protection, and the reaction is carried out for 10-15 hours at a speed of 60-80 r / min and a temperature of 80-85° C. to obtain a diamine-terminated polysiloxane;
[0017] Step B2: 1,3-dibromopropanol, N,N-dimethyldodecylamine and n-propanol are mixed evenly, reacted at a speed of 60-80 r / min and a temperature of 96-98° C. for 10-15 hours, and then acryloyl chloride is added and the reaction is continued for 3-5 hours to obtain intermediate 1. Intermediate 1, diamine-terminated polysiloxane and Custer catalyst are mixed evenly, nitrogen is introduced for protection, and the reaction is carried out at a speed of 120-150 r / min and a temperature of 100-105° C. for 40-50 hours to obtain modified polysiloxane;
[0018] Step B3: Mix tannic acid, monochloroacetic acid and deionized water evenly, add sodium carbonate to keep the pH neutral, react for 3-5 hours at a speed of 150-200 r / min and a temperature of 50-55° C., adjust the pH to acidic to obtain carboxylated tannic acid, mix carboxylated tannic acid, modified polysiloxane, DCC and DMF evenly, react for 6-8 hours at a speed of 120-150 r / min and a temperature of 30-40° C. to obtain a hyperbranched amine.
[0019] Furthermore, the molar ratio of octamethylcyclotetrasiloxane, tetramethyltetrahydrocyclotetrasiloxane and 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane described in step B1 is 4:2:1, and the amount of CT175 used is 1-1.5% of the total mass of octamethylcyclotetrasiloxane, tetramethyltetrahydrocyclotetrasiloxane and 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane.
[0020] Furthermore, the molar ratio of 1,3-dibromopropanol, N,N-dimethyldodecylamine and acryloyl chloride in step B2 is 1:2:1, the molar ratio of Si-H bonds on intermediate 1 and diamine-terminated polysiloxane is 1.2:1, and the amount of Custer catalyst used is 0.5% by mass of intermediate 1 and diamine-terminated polysiloxane.
[0021] Furthermore, the molar ratio of tannic acid to monochloroacetic acid in step B3 is 1:3, the mass fraction of the sodium carbonate aqueous solution is 30%, and the molar ratio of the carboxyl group on the carboxylated tannic acid, the amino group on the modified polysiloxane and DCC is 1:2:1.1.
[0022] Beneficial effects of the invention: a negative hard water corrosion inhibitor prepared by the invention comprises the following raw materials: polyepoxysuccinic acid, a scale inhibitor dispersant, a zinc salt, an organic carboxylate, an azole, a synergist and water; the synergist is reacted with maleic anhydride and urea as raw materials to obtain polysuccinimide; polysuccinimide is grafted with diethylenetriamine under alkaline conditions so that the side chain contains an active amino group to obtain a modifier; hyperbranched amine is reacted with cyanuric chloride, and a chlorine atom site on the cyanuric chloride is reacted by temperature control; a modifier is added so that the amino group on the modifier reacts with the remaining chlorine atom sites to obtain a synergist; hyperbranched amine is reacted with octamethylcyclotetrasiloxane, tetramethyltetrahydrocyclotetrasiloxane and 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane to obtain a diamine-terminated polysiloxane; 1,3-dibromopropanol and N,N-dimethyldodecylamine are reacted to form a quaternary ammonium salt structure structure, and then adding acryloyl chloride and alcohol hydroxyl to react to obtain intermediate 1, and the intermediate 1 and diamine-terminated polysiloxane are treated with a Custer catalyst to graft the double bond on the intermediate 1 with the Si-H on the diamine-terminated polysiloxane to obtain modified polysiloxane, and tannic acid is treated with monochloroacetic acid to graft carboxyl groups on the tannic acid molecules to obtain carboxylated tannic acid, and the carboxylated tannic acid and modified polysiloxane are subjected to a dehydration reaction to obtain hyperbranched amine. The synergist contains a quaternary ammonium salt structure. Since the electronegativity of bromide ions is small and the repulsion between ions is weak, the synergist can be adsorbed on the metal surface to form an adsorption layer. At the same time, the synergist contains a large amount of organic silicon segments and hyperbranched structures, so that the synergist can form a dense organic silicon film on the metal surface, thereby preventing the metal surface from directly contacting with water, and a large amount of catechol structures can increase the adsorption of the synergist and the metal surface, avoiding the shedding of the organic silicon film. DETAILED DESCRIPTION
[0023] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention. Example
[0024] A method for preparing a negative hard water corrosion inhibitor comprises the following steps:
[0025] Weigh the following raw materials in percentage: 5% polyepoxysuccinic acid, 5% scale inhibitor and dispersant, 5% zinc salt, 10% organic carboxylate, 0.1% azole and 10% synergist, and the balance is water, mix the raw materials evenly to prepare a negative hard water corrosion inhibitor.
[0026] The polyepoxysuccinic acid is a commercially available liquid preparation with a solid content of 40% and a polymerization degree n ranging from an integer of 10 to 50; the scale inhibitor and dispersant is an acrylic copolymer with AMPS; the zinc salt is zinc chloride; the organic carboxylate is polyacrylic acid sodium salt; and the azole is benzotriazole.
[0027] The synergist is prepared by the following steps:
[0028] Step A1: maleic anhydride, deionized water and urea are mixed, stirred at a speed of 120 r / min and a temperature of 60° C. for 40 min, then heated to 130° C., a mixed acid solution is added, and the temperature is raised to 180° C. for reaction for 2 h to obtain polysuccinimide;
[0029] Step A2: polysuccinimide, diethylenetriamine and deionized water are uniformly mixed, stirred and sodium hydroxide solution is added at a speed of 150 r / min and a temperature of 60° C., reacted for 15 hours, and then the pH value is adjusted to neutral to obtain a modifier;
[0030] Step A3: Mix the hyperbranched amine, cyanuric chloride, sodium hydroxide and acetone evenly, react for 2 hours at a speed of 120 r / min and a temperature of 0° C., add a modifier, raise the temperature to 80° C., and continue to react for 2 hours to obtain a synergist.
[0031] The dosage ratio of maleic anhydride, deionized water, urea and mixed acid described in step A1 is 100 mmol:10 mL:70 mmol:1 mL, and the mixed acid is phosphoric acid and sulfuric acid mixed in a volume ratio of 1:1.
[0032] The usage ratio of the polysuccinimide, diethylenetriamine and sodium hydroxide solution in step A2 is 2g:1.5g:5mL, and the concentration of the sodium hydroxide solution is 2.5mol / L.
[0033] The amount ratio of the hyperbranched amine, cyanuric chloride, sodium hydroxide and modifier described in step A3 is 2g:10mmol:30mmol:20mmol.
[0034] The hyperbranched amine is prepared by the following steps:
[0035] Step B1: octamethylcyclotetrasiloxane, tetramethyltetrahydrocyclotetrasiloxane, 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane and ion exchange resin CT175 were uniformly mixed, nitrogen was introduced for protection, and the reaction was carried out at a speed of 60 r / min and a temperature of 80° C. for 10 hours to obtain a diamine-terminated polysiloxane;
[0036] Step B2: 1,3-dibromopropanol, N,N-dimethyldodecylamine and n-propanol were mixed evenly, reacted at a speed of 60 r / min and a temperature of 96° C. for 10 h, and then acryloyl chloride was added and the reaction was continued for 3 h to obtain intermediate 1. Intermediate 1, diamine-terminated polysiloxane and Custer catalyst were mixed evenly, nitrogen was introduced for protection, and the reaction was carried out at a speed of 120 r / min and a temperature of 100° C. for 40 h to obtain modified polysiloxane;
[0037] Step B3: Mix tannic acid, monochloroacetic acid and deionized water evenly, add sodium carbonate to keep the pH neutral, react for 3 hours at a speed of 150 r / min and a temperature of 50°C, adjust the pH to acidic, and obtain carboxylated tannic acid; mix carboxylated tannic acid, modified polysiloxane, DCC and DMF evenly, and react for 6 hours at a speed of 120 r / min and a temperature of 30°C to obtain hyperbranched amines.
[0038] The molar ratio of octamethylcyclotetrasiloxane, tetramethyltetrahydrocyclotetrasiloxane and 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane described in step B1 is 4:2:1, and the amount of CT175 used is 1% of the total mass of octamethylcyclotetrasiloxane, tetramethyltetrahydrocyclotetrasiloxane and 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane.
[0039] The molar ratio of 1,3-dibromopropanol, N,N-dimethyldodecylamine and acryloyl chloride described in step B2 is 1:2:1, the molar ratio of Si-H bonds on intermediate 1 and diamine-terminated polysiloxane is 1.2:1, and the amount of Custer catalyst used is 0.5% by mass of intermediate 1 and diamine-terminated polysiloxane.
[0040] The molar ratio of tannic acid to monochloroacetic acid in step B3 is 1:3, the mass fraction of the sodium carbonate aqueous solution is 30%, and the molar ratio of the carboxyl group on the carboxylated tannic acid, the amino group on the modified polysiloxane and DCC is 1:2:1.1. Example
[0041] A method for preparing a negative hard water corrosion inhibitor comprises the following steps:
[0042] Weigh the following raw materials in percentage: 10% polyepoxysuccinic acid, 10% scale inhibitor and dispersant, 8% zinc salt, 25% organic carboxylate, 0.3% azole and 13% synergist, and the balance is water, mix the raw materials evenly to prepare a negative hard water corrosion inhibitor.
[0043] The polyepoxysuccinic acid is a commercially available liquid preparation with a solid content of 40% and a polymerization degree n ranging from an integer of 10 to 50; the scale inhibitor and dispersant is an acrylic copolymer with AMPS; the zinc salt is zinc chloride; the organic carboxylate is the sodium salt of benzoic acid; and the azole is mercaptobenzothiazole.
[0044] The synergist is prepared by the following steps:
[0045] Step A1: maleic anhydride, deionized water and urea are mixed, stirred at a speed of 120 r / min and a temperature of 65° C. for 45 min, then heated to 135° C., a mixed acid solution is added, and the temperature is raised to 183° C. for reaction for 3 h to obtain polysuccinimide;
[0046] Step A2: polysuccinimide, diethylenetriamine and deionized water are uniformly mixed, stirred and sodium hydroxide solution is added at a speed of 150 r / min and a temperature of 63° C., reacted for 18 hours, and then the pH value is adjusted to neutral to obtain a modifier;
[0047] Step A3: Mix the hyperbranched amine, cyanuric chloride, sodium hydroxide and acetone evenly, react for 2.5 hours at a speed of 120 r / min and a temperature of 3° C., add a modifier, raise the temperature to 85° C., and continue to react for 2.5 hours to obtain a synergist.
[0048] The dosage ratio of maleic anhydride, deionized water, urea and mixed acid described in step A1 is 100 mmol:10 mL:70 mmol:1 mL, and the mixed acid is phosphoric acid and sulfuric acid mixed in a volume ratio of 1:1.
[0049] The usage ratio of the polysuccinimide, diethylenetriamine and sodium hydroxide solution in step A2 is 2g:1.5g:5mL, and the concentration of the sodium hydroxide solution is 2.5mol / L.
[0050] The amount ratio of the hyperbranched amine, cyanuric chloride, sodium hydroxide and modifier described in step A3 is 2g:10mmol:30mmol:20mmol.
[0051] The hyperbranched amine is prepared by the following steps:
[0052] Step B1: octamethylcyclotetrasiloxane, tetramethyltetrahydrocyclotetrasiloxane, 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane and ion exchange resin CT175 were uniformly mixed, nitrogen was introduced for protection, and the reaction was carried out at a speed of 60 r / min and a temperature of 83° C. for 13 hours to obtain a diamine-terminated polysiloxane;
[0053] Step B2: 1,3-dibromopropanol, N,N-dimethyldodecylamine and n-propanol were mixed evenly, reacted at a speed of 60 r / min and a temperature of 97°C for 13 hours, acryloyl chloride was added, and the reaction was continued for 4 hours to obtain intermediate 1, intermediate 1, diamine-terminated polysiloxane and Custer catalyst were mixed evenly, nitrogen was introduced for protection, and the reaction was carried out at a speed of 150 r / min and a temperature of 103°C for 45 hours to obtain modified polysiloxane;
[0054] Step B3: Mix tannic acid, monochloroacetic acid and deionized water evenly, add sodium carbonate to keep the pH neutral, react for 4 hours at a speed of 200 r / min and a temperature of 53°C, adjust the pH to acidic, and obtain carboxylated tannic acid; mix carboxylated tannic acid, modified polysiloxane, DCC and DMF evenly, and react for 7 hours at a speed of 120 r / min and a temperature of 35°C to obtain hyperbranched amines.
[0055] The molar ratio of octamethylcyclotetrasiloxane, tetramethyltetrahydrocyclotetrasiloxane and 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane described in step B1 is 4:2:1, and the amount of CT175 used is 1.3% of the total mass of octamethylcyclotetrasiloxane, tetramethyltetrahydrocyclotetrasiloxane and 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane.
[0056] The molar ratio of 1,3-dibromopropanol, N,N-dimethyldodecylamine and acryloyl chloride described in step B2 is 1:2:1, the molar ratio of Si-H bonds on intermediate 1 and diamine-terminated polysiloxane is 1.2:1, and the amount of Custer catalyst used is 0.5% by mass of intermediate 1 and diamine-terminated polysiloxane.
[0057] The molar ratio of tannic acid to monochloroacetic acid in step B3 is 1:3, the mass fraction of the sodium carbonate aqueous solution is 30%, and the molar ratio of the carboxyl group on the carboxylated tannic acid, the amino group on the modified polysiloxane and DCC is 1:2:1.1. Example
[0058] A method for preparing a negative hard water corrosion inhibitor comprises the following steps:
[0059] Weigh the following raw materials in percentage: 15% polyepoxysuccinic acid, 15% scale inhibitor and dispersant, 10% zinc salt, 40% organic carboxylate, 0.5% azole and 15% synergist, and the balance is water, mix the raw materials evenly to prepare a negative hard water corrosion inhibitor.
[0060] The polyepoxysuccinic acid is a commercially available liquid preparation with a solid content of 40% and a polymerization degree n ranging from an integer of 10 to 50; the scale inhibitor and dispersant is an acrylic copolymer with AMPS; the zinc salt is zinc sulfate; the organic carboxylate is carboxymethyl cellulose; and the azole is benzotriazole.
[0061] The synergist is prepared by the following steps:
[0062] Step A1: maleic anhydride, deionized water and urea are mixed, stirred at a speed of 150 r / min and a temperature of 70° C. for 50 min, then heated to 140° C., a mixed acid solution is added, and the temperature is raised to 185° C. for reaction for 3 h to obtain polysuccinimide;
[0063] Step A2: polysuccinimide, diethylenetriamine and deionized water are uniformly mixed, stirred and sodium hydroxide solution is added at a speed of 200 r / min and a temperature of 65° C., reacted for 20 hours, and then the pH value is adjusted to neutral to obtain a modifier;
[0064] Step A3: Mix the hyperbranched amine, cyanuric chloride, sodium hydroxide and acetone evenly, react for 3 hours at a speed of 150 r / min and a temperature of 5° C., add a modifier, raise the temperature to 90° C., and continue to react for 3 hours to obtain a synergist.
[0065] The dosage ratio of maleic anhydride, deionized water, urea and mixed acid described in step A1 is 100 mmol:10 mL:70 mmol:1 mL, and the mixed acid is phosphoric acid and sulfuric acid mixed in a volume ratio of 1:1.
[0066] The usage ratio of the polysuccinimide, diethylenetriamine and sodium hydroxide solution in step A2 is 2g:1.5g:5mL, and the concentration of the sodium hydroxide solution is 2.5mol / L.
[0067] The amount ratio of the hyperbranched amine, cyanuric chloride, sodium hydroxide and modifier described in step A3 is 2g:10mmol:30mmol:20mmol.
[0068] The hyperbranched amine is prepared by the following steps:
[0069] Step B1: octamethylcyclotetrasiloxane, tetramethyltetrahydrocyclotetrasiloxane, 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane and ion exchange resin CT175 were uniformly mixed, nitrogen was introduced for protection, and the reaction was carried out at a speed of 80 r / min and a temperature of 85° C. for 15 hours to obtain a diamine-terminated polysiloxane;
[0070] Step B2: 1,3-dibromopropanol, N,N-dimethyldodecylamine and n-propanol were mixed evenly, reacted at a speed of 80 r / min and a temperature of 98° C. for 15 h, acryloyl chloride was added, and the reaction was continued for 5 h to obtain intermediate 1, intermediate 1, diamine-terminated polysiloxane and Custer catalyst were mixed evenly, nitrogen was introduced for protection, and the reaction was carried out at a speed of 150 r / min and a temperature of 105° C. for 50 h to obtain modified polysiloxane;
[0071] Step B3: Mix tannic acid, monochloroacetic acid and deionized water evenly, add sodium carbonate to keep the pH neutral, react for 5 hours at a speed of 200 r / min and a temperature of 55°C, adjust the pH to acidic, and obtain carboxylated tannic acid; mix carboxylated tannic acid, modified polysiloxane, DCC and DMF evenly, and react for 8 hours at a speed of 150 r / min and a temperature of 40°C to obtain hyperbranched amines.
[0072] The molar ratio of octamethylcyclotetrasiloxane, tetramethyltetrahydrocyclotetrasiloxane and 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane described in step B1 is 4:2:1, and the amount of CT175 used is 1.5% of the total mass of octamethylcyclotetrasiloxane, tetramethyltetrahydrocyclotetrasiloxane and 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane.
[0073] The molar ratio of 1,3-dibromopropanol, N,N-dimethyldodecylamine and acryloyl chloride described in step B2 is 1:2:1, the molar ratio of Si-H bonds on intermediate 1 and diamine-terminated polysiloxane is 1.2:1, and the amount of Custer catalyst used is 0.5% by mass of intermediate 1 and diamine-terminated polysiloxane.
[0074] The molar ratio of tannic acid to monochloroacetic acid in step B3 is 1:3, the mass fraction of the sodium carbonate aqueous solution is 30%, and the molar ratio of the carboxyl group on the carboxylated tannic acid, the amino group on the modified polysiloxane and DCC is 1:2:1.1.
[0075] Comparative Example 1
[0076] Compared with Example 1, no synergist was added in this comparative example, and the remaining steps were the same.
[0077] Comparative Example 2
[0078] Compared with Example 1, no hyperbranched amine was added in this comparative example, and the remaining steps were the same.
[0079] Comparative Example 3
[0080] Compared with Example 1, this comparative example does not add ethylenediamine to replace the modified polysiloxane, and the remaining steps are the same.
[0081] The corrosion inhibitors prepared in Examples 1-3 and Comparative Examples 1-3 were used in accordance with the standard of GB / T18175-2014. At a temperature of 45°C, Q235A carbon steel was immersed in 3wt%, 5wt%, 10wt% and 25wt% sodium chloride solutions for 24 hours, respectively. The dosage of the negative hard water corrosion inhibitor was 10 g / L. The test results are shown in the following table.
[0082] Example 1 Example 2 Example 3 Comparative Example 1 Comparative Example 2 Comparative Example 3 3wt% corrosion inhibition rate 98.36 98.59 98.83 87.14 91.01 92.14 5wt% corrosion inhibition rate 97.58 97.71 97.94 86.65 89.35 89.78 10wt% corrosion inhibition rate 95.81 96.01 96.32 84.35 86.28 87.37 25wt% corrosion inhibition rate 92.43 92.58 93.15 82.93 84.47 85.91
[0083] It can be seen from the above table that this application has a very good corrosion inhibition effect.
[0084] The above contents are merely examples and explanations of the concept of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the concept of the invention or exceed the scope defined by the claims, they shall all fall within the protection scope of the present invention.
Claims
1. A method for preparing a negative hard water corrosion inhibitor, characterized in that: The specific steps include: Weigh the following percentages of raw materials: 5-15% polyepoxysuccinic acid, 5-15% scale inhibitor and dispersant, 5-10% zinc salt, 10-40% organic carboxylate, 0.1-0.5% azole and 10-15% synergist, the balance being water, mix the raw materials evenly to prepare a negative hard water corrosion inhibitor; The polyepoxysuccinic acid is a commercially available liquid preparation with a solid content of 40% and a degree of polymerization n ranging from an integer of 10 to 50; the scale inhibitor is an acrylic copolymer with AMPS; the zinc salt is one of zinc chloride or zinc sulfate; the organic carboxylate is one of polyacrylic acid, benzoic acid and a sodium salt of a copolymer containing a sulfonic acid group or carboxymethyl cellulose; the azole is one of benzotriazole and mercaptobenzoxazole; The synergist is prepared by the following steps: Step A1: maleic anhydride, deionized water and urea are mixed and stirred, then the temperature is raised and a mixed acid solution is added to react to obtain polysuccinimide; Step A2: polysuccinimide, diethylenetriamine and deionized water are mixed and stirred, and a sodium hydroxide solution is added to react, and then the pH value is adjusted to be neutral to obtain a modifier; Step A3: After the hyperbranched amine, cyanuric chloride, sodium hydroxide and acetone are mixed and reacted, a modifier is added, and the temperature is raised to continue the reaction to obtain a synergist; The hyperbranched amine is prepared by the following steps: Step B1: octamethylcyclotetrasiloxane, tetramethyltetrahydrocyclotetrasiloxane, 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane and ion exchange resin CT175 are uniformly mixed, nitrogen is introduced for protection, and a reaction is carried out to obtain a diamine-terminated polysiloxane; Step B2: After 1,3-dibromopropanol, N,N-dimethyldodecylamine and n-propanol are mixed for reaction, acryloyl chloride is added and the reaction is continued to obtain intermediate 1, and intermediate 1, diamine-terminated polysiloxane and Custer catalyst are mixed for reaction to obtain modified polysiloxane; Step B3: Tannic acid, monochloroacetic acid and deionized water are mixed evenly, sodium carbonate is added to keep the pH at neutral, the reaction is carried out, and the pH is adjusted to be acidic to obtain carboxylated tannic acid. The carboxylated tannic acid, modified polysiloxane, DCC and DMF are mixed and reacted to obtain hyperbranched amine.
2. The method for preparing a negative hard water corrosion inhibitor according to claim 1, characterized in that: The dosage ratio of maleic anhydride, deionized water, urea and mixed acid described in step A1 is 100 mmol:10 mL:70 mmol:1 mL, and the mixed acid is phosphoric acid and sulfuric acid mixed in a volume ratio of 1:
1.
3. The method for preparing a negative hard water corrosion inhibitor according to claim 1, characterized in that: The usage ratio of polysuccinimide, diethylenetriamine and sodium hydroxide solution in step A2 is 2g:1.5g:5mL.
4. The method for preparing a negative hard water corrosion inhibitor according to claim 1, characterized in that: The amount ratio of the hyperbranched amine, cyanuric chloride, sodium hydroxide and modifier described in step A3 is 2g:10mmol:30mmol:20mmol.
5. The method for preparing a negative hard water corrosion inhibitor according to claim 1, characterized in that: The molar ratio of octamethylcyclotetrasiloxane, tetramethyltetrahydrocyclotetrasiloxane and 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane described in step B1 is 4:2:
1.
6. The method for preparing a negative hard water corrosion inhibitor according to claim 1, characterized in that: The molar ratio of 1,3-dibromopropanol, N,N-dimethyldodecylamine and acryloyl chloride in step B2 is 1:2:1, and the molar ratio of the intermediate 1 and the Si-H bond on the diamine-terminated polysiloxane is 1.2:
1.
7. The method for preparing a negative hard water corrosion inhibitor according to claim 1, characterized in that: The molar ratio of tannic acid to monochloroacetic acid in step B3 is 1:3, the mass fraction of the sodium carbonate aqueous solution is 30%, and the molar ratio of the carboxyl group on the carboxylated tannic acid, the amino group on the modified polysiloxane and DCC is 1:2:1.
1.
8. A negative hard water corrosion inhibitor, characterized in that: Prepared according to any one of the preparation methods described in claims 1-7.
Citation Information
Patent Citations
Polyaspartic acid / diethylenetriamine grafted copolymer and synthetic method thereof
CN104250378A
Preparation method of non-phosphorus corrosion and scale inhibitor
CN104355418A